Cost-effectiveness of immune checkpoint inhibitors in treating metastatic urothelial cancer - Yang, Li-Yu; Li, Jian-Ri; Chen, Chuan-Shu; Cheng, Chen-Li; Hung, Sheng-Chun; Chiu, Kun-Yuan; Yang, Cheng-Kuang; Hsu, Chiann-Yi; Wang, Shian-Shiang (Frontiers in Pharmacology, 2024)
Objectives: Immune checkpoint inhibitor (ICI) is an important treatment option for metastatic urothelial carcinoma (mUC) patients. A lot of clinical evidence proved the survival benefits of ICI, but cost-effectiveness of the treatment remains unclear. This study evaluates the cost-effectiveness of the ICIs treatment in different sequences among mUC patients. Methods: We retrospectively analyzed mUC patients who had been treated at our hospital between January 2016 and December 2020. These patients received chemotherapy with or without ICI treatment (Pembrolizumab, Atezolizumab, Nivolumab, Durvalumab, or Avelumab). The patients were divided into three different groups: receiving chemotherapy alone, receiving a combination of first-line ICI and chemotherapy (ICI combination therapy), and receiving chemotherapy as the first-line treatment followed by second-line ICI therapy (Subsequent ICI therapy). The primary endpoint was cost per life day, while lifetime medical costs and overall survival were also evaluated. Results: The 74 enrolled patients had a median age of 67.0 years, with 62.2% being male. Of these patients, 23 had received chemotherapy only, while the remaining patients had received combined therapy with ICI in either first-line or as subsequent agents (37 patients had ever received atezolizumab, 18 pembrolizumab, 1 Durvalumab, 1 Nivolumab, and 1 Avelumab separately.). Fifty-five patients (74.3%, 55/74) received cisplatin amongst all the patients who underwent chemotherapy. Median overall survival was 27.5 months (95% CI, 5.2 to 49.9) in the first-line ICI combination therapy group, and 8.9 months (95% CI, 7.1 to 10.8) in the chemotherapy only. Median overall survival for the subsequent ICI therapy group was not reached. The median lifetime cost after metastatic UC diagnosis was USD 31,221. The subsequent ICI therapy group had significantly higher costs when compared with the ICI combination therapy group (155.8 USD per day, [IQR 99.0 to 220.5] v 97.8 USD per day, [IQR 60.8 to 159.19], p=0.026). Higher insurance reimbursement expenses for the subsequent ICI therapy group were observed when compared with the ICI combination therapy group. Conclusions: Our real-world data suggests that first line use of ICI combined with chemotherapy demonstrates better cost-effectiveness and similar survival outcomes for mUC patients, when compared with subsequent ICI therapy after chemotherapy.